Pengaruh Penggunaan E-Modul Berb Pengaruh Penggunaan E-Modul Berbasis Masalah Terhadap Hasil Belajar Biologi Kelas XI SMA Negeri 3 Pematangsiantar: Pengaruh Penggunaan E-Modul Berbasis Masalah Terhadap Hasil Belajar Biologi Kelas XI SMA Negeri 3 Pematangsiantar - Silaban, Winarto; Siagian, Gunaria (UNIB Press, 2024)
This research explains and describes the research data, namely through comparison scores between pre-test and post-test scores, where the pre-test is carried out before starting the lesson and the post-test is carried out after the lesson is carried out in both classes, namely the experimental class and the control class. The results of this research indicate success in implementing problem-based e-book media on student activities and learning outcomes in immune system material at SMA Negeri 3 Pematangsiantar city. This success is proven by an increase in the value of student learning outcomes with the criteria being quite effective with a mean value of 63.20% with a standard deviation of 12,348 and a significant difference in the conduciveness of learning activities which is stated to be good with a mean value of 78.14% with the standard deviation of 15,786. The application of e-book media can also increase students' knowledge about digital literacy education, where by implementing e-book learning media, students not only increase their knowledge of science but are also increasingly formed into a young generation who are able to go hand in hand with technological developments.